2017
DOI: 10.1111/apa.13761
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study shows that doxapram therapy avoided the need for endotracheal intubation in most premature neonates

Abstract: Oral and intravenous doxapram effectively treated most cases of apnoea in preterm infants, avoiding the need for intubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…Previous studies have shown that doxapram reduces apnea frequency and the need for invasive mechanical ventilation [4]. However, a recent systematic review, based on a small number of studies with mainly low quality of evidence, indicated that no firm conclusions can be drawn on the efficacy and safety of doxapram [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that doxapram reduces apnea frequency and the need for invasive mechanical ventilation [4]. However, a recent systematic review, based on a small number of studies with mainly low quality of evidence, indicated that no firm conclusions can be drawn on the efficacy and safety of doxapram [7].…”
Section: Discussionmentioning
confidence: 99%
“…Doxapram is an analeptic drug that stimulates peripheral chemoreceptors in the carotid bodies as well as the central chemoreceptors in the respiratory center in the brainstem [3]. Previous research has shown that infusion of doxapram is effective in reducing apneic events and preventing respiratory insufficiency requiring intubation and invasive mechanical ventilation [4]. Furthermore, some small physiological studies have shown an increase in minute ventilation and tidal volume after infusion of doxapram, but only if dosed > 1 mg/kg/h [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…A positive effect of doxapram and-to a lesser extent of keto-doxapram-on the respiratory drive was also found in newborn lambs (Bairam et al, 1990). Two retrospective studies concluded that doxapram therapy may avoid mechanical ventilation (Prins et al, 2013;Flint et al, 2017a). In our earlier studies, doxapram therapy had a positive effect on the SpO 2 , the applied FiO 2 (Flint et al, 2017b), the oxygen need (SpO 2 /FiO 2 ratio), and hypoxia (cumulative oxygen shortage under the 89% limit) (Poppe et al, 2019).…”
Section: Discussionmentioning
confidence: 78%
“…In summary, it appears that doxapram therapy is beneficial in infants with persistent AOP despite caffeine and optimal care, but randomized controlled trials are lacking, and the late outcomes of premature infants treated with doxapram for AOP are unclear. 77,[79][80][81]…”
Section: Doxaprammentioning
confidence: 99%